"On Engineering Night the crowd watches a pour in the Foundry," circa 1930 - Munro, Melville S. (Tufts Archival Research Center, 2005)
5 x 4, mounted on 8 x 10 in: M. S. Munro, Miscellaneous pictures through the years, Vol. 1, p.7